Keupayaan mengintegrasikan teknologi multimedia di kalangan guru sekolah menengah dalam pengajaran - Zarimah Sham, Ramli (2008)
The aim of this study was to identify the abilities of the teachers in integrating multimedia technology into teaching and learning in secondary school. The 120 Malaysian teachers chosen and participated as respondents in order to obtain their views concerning utilization of multimedia technology in their daily teaching practices. The instrument used was a questionnaire to probe teachers' demography, training, attitudes, teachers' ICT hardware skills, standards of hardware and software as well as the use of multimedia-based content. The data collected were analyzed using Statistical Packages for the Social Sciences (SPSS) version 14.0. The design of this study was in the form of descriptive statistics to report the score, percentage, frequency, mean, ANOVA and ttest. The findings of this study reveal that: (a) teachers were ready to use multimedia technology and multimedia-based contents in their daily lessons, (b) teachers who were facing some problems in integrating multimedia technology were also lacking some ICT skills, needing some guidance and needing to acquire some abilities in handling and utilising hardware and software, (c) facilities concerning multimedia technology was not enough for the teachers to integrate multimedia technology in their teaching and learning and (d) time constraint. The study provides some significant evidences regarding their positive attitudes toward the utilisation of multimedia technology and their readiness to use multimedia technology in their classrooms. This study also offers some suggestions . on ways to increase the utilisation of multimedia technology in secondary schools. The suggestions include the importance of designing and carrying out short courses pertaining to multimedia technology integration, improving teachers' abilities and skills in utilising hardware and other multimedia technology equipment, involving more teachers to develop multimedia-based materials for students of various learning styles and monitoring of teachers' application of multimedia technology in teaching and learning by school administrators as well as officers from state education departments and ministry. In conclusion, facilities, training programmes, technology multimedia infrastructure and demography were considered factors that relate to educational change in the era of multimedia technology.